Tinjauan Literatur Naratif: Inovasi dalam Manajemen Nyeri Postoperatif Berbasis Digital - Nurul Imam; Pradita Ayu Fernanda; Khalifatus Zuhriyah Alfianti; Eka Mei Dianita; Ni Putu Diah Ayu Rusmeni (Health and Technology Journal (HTechJ), 2024)
Effective postoperative pain management is a key element in patient recovery after surgery, but often standard protocols do not take advantage of the potential of real-time data and digital technology for more responsive therapy adjustments. The aim of this study was to identify the latest innovations in digital-based postoperative pain management. A literature review examined the use of digital technology in postoperative pain management, focusing on smartphone apps, wearable devices, and real-time data analytics for monitoring patient pain with the keywords "Pain Management AND Digital Postoperative" OR "Digital Health AND Pain Management" AND "Technology" OR "Information Systems". The year of the source of the literature taken is 2019-2024. Database searches use Scopus, Pub Med, Sage Journal, and Google Scholar. The findings of this review suggest that the integration of digital technology in postoperative pain management can improve the personalization of care by allowing for more accurate and responsive therapy adjustments to changes in patients' pain conditions. Data-Based Approaches in the Digital Era are Virtual Reality (VR), PASHA Application (pain assessment, stimulating and healing application), A wireless intelligent PCA (Wi-PCA) AI (Artificial Intelligence), Cell Phone Application, Wearable Devices, Mhealth, NeuroCuple, LINE, Digital Intervention Group, The Panda App and A Digital Application. Wearable apps and devices effectively monitor pain and enable real-time therapy adjustments. Digital-based innovation can be used as an alternative nursing intervention for post-operative pain management.